Marcha, capacidade funcional e risco de quedas em indivíduos com glaucoma primário de ângulo aberto em estágios inicial e moderado: parâmetros temporais e espaciais da marcha de idosas brasileiras comunitárias - Henrique de Alencar Gomes (2015)
Study 1 - Gait parameters, functional mobility and fall risk in individuals with early to moderate primary open angle glaucoma: a cross-sectional study Glaucoma stands out as one of the leading causes of irreversible blindness in Brazil and worldwide. Primary Open-Angle Glaucoma (POAG) is often called the silent blinder because, during the early to moderate stages of the disease, there are usually no noticeable symptoms. However, findings indicating early deterioration of visual quality have been evidenced in these early stages of glaucoma. It is unknown whether early visual dysfunctions due to POAG could have a negative influence on functional outcomes and falls in those individuals. The purpose of this observational study was to investigate the influence of early to moderate POAG on gait parameters, functional mobility and fall risk in community-dwelling adults. Data from 67 participants divided in a POAG group (33) and a control group (34) were analyzed. Fall risk was measured using the short form of the Physiological Profile Assessment composed of following tests contrast sensitivity, proprioception, muscle strength of knee extensors, manual reaction time and postural sway over the foam with open eyes. Spatiotemporal parameters of gait were measured using GAITRite® system. Functional measures were obtained with the Timed Up and Go (TUG) test, the Five-Repetition Sit-To-Stand test and the Dynamic Gait Index. Data from POAG and control groups were presented as mean and standard deviation for continuous variables and absolute and relative frequencies for categorical variables. Sociodemographic, anthropometric, clinical and ophthalmologic characteristics were analyzed by the means difference between groups with a 95% confidence interval and the chi-square test. The Principal Component Analysis (PCA) was applied to 16 gait, functional and PPA variables. The scores of the resulting principal components (PC) were standardized to z-scores (mean of zero and standard deviation of 1) and a 95% confidence interval was performed to determine which CP were different between groups. Then, a global score was obtained by summing CP of the identified significant CP, dividing by the total number of CP, and calculating accordingly a new z-score. The CP global scores were used to compare the groups, considering the clinical interpretation of the CP. Then, a multivariate analysis of variance was performed with the primary contributing variables (weight coefficient 0.30) of significant CP to determine which variables were different between the control group and POAG. All tests were analyzed with a significance level 0.05. The groups showed no significant differences in gender, age and body mass index. Principal component analysis reduced the data and identified three components - balance, reaction and mobility - that were significantly different between groups. In addition, the variables contrast sensitivity, proprioception and the TUG test, which contributed heavily to the significant components, were also different between groups. The glaucoma group had a greater risk of falls compared to the control group, but number of fallers and number of falls in the past 12 months and fear of falling were similar between groups. Individuals in the early and moderate stages of POAG presented balance, mobility and reaction deficits and a higher risk of falling. According to our knowledge, this is the first study to apply the PPA in a group of individuals at the early and moderate stages of POAG. It is also the first study that was able to identify three important components - balance, reaction and mobility - based on a data reduction analysis, in individuals with visual deficit. The results of this study places emphasis on an early diagnosis of glaucoma and the development of a fall-prevention program focused on maintaining and/or improving balance, reaction and mobility performance in this population. Study 2 - Normative spatiotemporal gait data in Brazilian females community-dwelling older adults Traditionally, gait velocity is the elected parameter used to assess gait due to the link to adverse outcomes in the elderly. However, gait is an extremely complex motor task that can be expressed by other spatiotemporal parameters and its variability. Most studies are focused on gait velocity, neglecting those other gait parameters. In addition, to our knowledge there is a lack of normative gait studies conducted in the community-dwelling older adults living in Brazil. The aim of this study was to provide normative values for the gait measurements obtained from a healthy Brazilian sample of Belo Horizonte community-dwelling elderly females between the ages of 65 to 89 years and to apply the Principal Component Analysis (PCA)-biplot approach to yield insight into different walking strategies that might occur during the aging process. A total of 305 independent community elderly were stratified into four age groups: 65-69 years (N = 103), 70-74 years (N = 95), 75-79 years (N = 77) and 80 years (N = 30). Age, height and body mass index were evaluated to describe the characteristics of the groups. Temporal and spatial gait parameters included velocity, cadence, stride length, support base, step time, swing time, support time and time dual support and were obtained using the GAITrite® system. Coefficient of variation (CV=[standard deviation/mean]x100) was used as a measure of gait variability for the following parameters: velocity (%CV), step length (%CV), base of support (%CV), step time (%CV), swing time (%CV), stance time (%CV) and double support time (%CV). The anthropometric characteristics and the spatiotemporal gait data of the participants were presented as mean and standard deviation. The principal component analysis (PCA) followed by interpretation of biplot approach were applied to 15 spatiotemporal parameters of gait. The resulting scores for each CP were standardized to z-scores (mean of zero and a standard deviation of 1) and a 95% confidence interval was performed to determine which CP were different among the groups. Then, multivariate analysis of variance (MANOVA) was performed to compare the primary contributing variables in each analyzed and significant component, and the age groups as the independent variable. For significant MANOVA, was performed Bonferroni correction. Finally, a biplot-ACP was built to assist in interpretation between the CP, the scores and the variables. All tests were analyzed with a significance level 0.05. A 95% confidence interval showed that only three components - rhythm, variability and support - that together explained 74.2% of the total variance in gait were different among the groups. The older age groups (75-79 and 80 years) walked with lower than average velocity, cadence and step length and were above average for the variables stance, step, swing and double support time. In addition, the 80 years age group presented the highest gait variability compared to the other groups. Aging is associated with decreased gait velocity and cadence and increased stance, step time and variability, but not associated with changes in base of support. Moreover, the PCA-biplot indicates a trend towards decreased rhythm and increased variability with aging. This information about the spatial and temporal parameters of gait may contribute to the assessment and rehabilitation of the elderly.